Impact of l1 on esl (english as a second language) writings of the undergraduates of university of jaffna - Sanmuganathan, K. (University of Jaffna, 2012)
The purpose of this study was to examine whether first language (L1) had an impact on the ESL (English as a Second Language) writings of the undergraduates of University of Jaffna. Most of the scholars in the fields of language learning and teaching give evidence for the L1-L2 comparison by the learners when they confronted with difficult grammatical forms and it is natural for the learners. Since this comparison is implicit, it may result in the formation of wrong rules due to an incomplete L2 knowledge. In this study, an investigation was made to identify the impact of L1 on ESL writings of the undergraduates of the University of Jaffna. The study involved qualitative methods of data collection. The data collected from the subjects’ responses were analyzed, and the findings were derived. The findings show that there are number of problems which are found to have impact on the learners’ ESL writings. Evidence provided by the written samples suggests that L1 played a role in the process of beginning ESL learners’ writing in English. Understanding linguistic differences between students’ L1 and English may help the learners to reduce the impact of L1.
Keywords: First language (L1); Second Language (L2); ESL writing; L1-L2 comparison; Difficult grammatical forms